2012
DOI: 10.4081/ijas.2012.e58
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cattle breed on finishing performance, carcass characteristics and economic benefits under typical beef production system in China

Abstract: This study compared the finishing performance carcass characteristics and economic benefits of two imported (Limousin and Simmental) and three local (Luxi, Jinnan and Qinchuan) cattle breeds slaughtered at 18.5 months of age under thetypical Chinese beef production system. All cattle (n=71) were reared under the same production system and fed the same finishing diet for 105 days. Eight bulls from each breed were randomly selected for slaughtering. Compared with the three local breeds, the two imported breeds h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…where ADG is the average daily gain (kg/head), MPBW is the average market price of body weight ($/kg), DMI is the daily DM intake (kg/head/d), and MPF is the market price of feeds ( Xie et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…where ADG is the average daily gain (kg/head), MPBW is the average market price of body weight ($/kg), DMI is the daily DM intake (kg/head/d), and MPF is the market price of feeds ( Xie et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…In China, local cattle breeds fed a mixture of straw and concentrates in typical Chinese production system had ADGs of between 0.78 and 0.82 kg day -1 , while a rate of 1.5 kg day -1 was reported for imported Limousin cattle [ 26 ]. Cross breeds have also been found to perform better than local breeds in China, reaching heavier slaughter weights at a younger age [ 27 ]. The introduction of new genetics, possibly through cross breeding local and imported cattle, may provide additional gains to better feeding and animal management in Sumbawa.…”
Section: Discussionmentioning
confidence: 99%
“…They found that some farmers prefer open grazing to cut-and-carry feeding, because of difficulties in meeting the much higher additional labour requirements of the latter system. Other reasons why farmers may resist adopting the new system include perceived higher risks of animal theft in the more built-up areas that feedlots tend to be located as well as a lack of capacity in tree establishment and access to seeds [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al (2012) ont comparé la vitesse de croissance et le rendement économique entre les taurillons (18,5 mois) de trois races locales (la Qinchuan, la Luxi et la Jin'nan) et de deux races importées (la Limousine et la Simmental) dans les mêmes conditions d'engraissement (typiques en Chine, tableau 1), le rendement économique étant calculé à partir de l'équation suivante :[(gain de poids pendant l'engraissement) × (prix par kg de poids vif)] / [coût des aliments pendant l'engraissement].Les résultats (tableau 2) ont montré que les deux races importées avaient une vitesse de croissance plus élevée (avec un gain journalier de 1,5 kg pour la race Limousine et 1,2 kg pour la race Simmental) que celle des races locales (0,78, 0,82 et 0,82 kg de gain journalier pour la race Qinchuan, Luxi et Jin'nan respectivement), et un meilleur rendement économique (1,89 et 1,68 pour la race Limousine et Simmental ; 1,52, 1,46 et 1,48 pour la race Qinchuan, Luxi et Jin'nan).…”
unclassified
“…Production de viande bovine en Chine et perspectives d'évolution / 265 Les performances d'engraissement des races importées et locales(Xie et al 2012).…”
unclassified